Futurism a very short introduction - Merjian, Ara H. 1974- (Oxford University Press, 2025)
From the motorcar to the radio, modern technology radically transformed urban life by the first decade of the twentieth century. This 'Very Short Introduction' explores the ideas, works, key figures, and development of the Futurist movement in Italy and beyond, in the context of the turmoil and rapid change of the early 20th century
Includes bibliographical references and index
Keywords: Art and Design / ukslc; History of art / thema; Futurism (Art) / Italy; Futurism (Art); Futurism (Literary movement) / Italy; Futurism (Literary movement); Futurism (Architecture) / Italy; Futurism (Architecture)